The effect of the meaning in grammatical analysis at AL-Baghdadi (1093 H) in a Khizanat al'adab. (Journal of Hama University, 2022)
The purpose of the research from this study is the reveal to extent of adoption of  Al- Baghdadi on meaning in his grammatical analysis in a Khizanat al'adab, and that's through comment on evidence by describing the meaning  as one of the foundations that controls in grammatical analysis